2015
DOI: 10.1038/gene.2015.34
|View full text |Cite
|
Sign up to set email alerts
|

Genetic epistasis between killer immunoglobulin-like receptors and human leukocyte antigens in Kawasaki disease susceptibility

Abstract: Kawasaki disease (KD) is a pediatric acute multisystemic vasculitis complicated by development of coronary artery lesions. The breakthrough theory on KD etiopathogenesis points to pathogens/environmental factors triggered by northeastern wind coming from China. Natural Killer cells and T lymphocytes express the inhibitory/activating Killer Immunoglobulin-like Receptors (KIR) to elicit an immune response against pathogens by binding to human leukocyte antigens (HLA) class I epitopes. We first report on the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…1 bottom). Consistent with our hypothesis, we previously found a high frequency of HLA-A*11 allele among KD patients compared to controls [9], thus confirming the overabundant presence of an HLA ligand for KIR3DL2.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…1 bottom). Consistent with our hypothesis, we previously found a high frequency of HLA-A*11 allele among KD patients compared to controls [9], thus confirming the overabundant presence of an HLA ligand for KIR3DL2.…”
supporting
confidence: 90%
“…Here, we tried to verify this genetic balance in KD children. We subdivided 100 KD children and 3533 healthy cord blood (CB) donors into the three HLA‐B Bw genotype groups, and analyzed the surrogate role of HLA‐A alleles coding ligands for KIR3DL1 and KIR3DL2 through their distribution in the three HLA‐B Bw genotype groups . All subjects were Caucasoids from Italy.…”
Section: Frequencies Of Hla‐a*03/*11 or Hla‐a*23/*24/*32 Carriers In mentioning
confidence: 99%
“…Several further evidence suggested that genetic determinants could contribute to the pathogenesis or progression of KD, such as: ( i ) the relationship found between interleukin IL‐1 polymorphisms and initial IVIG treatment failure in KD children , ( ii ) the finding that KCNN2 gene, a member of the KCNN family of potassium channel genes located on chromosome 5q22.3, could have a role as a new risk locus for coronary aneurysms , ( iii ) the genome‐wide association studies suggesting FCGR2A gene, encoding for low‐affinity immunoglobulin gamma Fc region receptor II‐a protein, as a susceptibility locus for KD onset and, finally, ( iv ) the hypothesis that genetic variations at the human leucocyte antigen (HLA) and killer immunoglobulin‐like receptors (KIR) loci could exert a modulatory activity either individually or in combination (HLA‐KIR epistasis) . Candidate genes in the etiopathogenesis of KD are listed in Table .…”
Section: Kawasaki Disease Featuresmentioning
confidence: 99%
“…HLA‐A, HLA‐B and HLA‐C polymorphisms were defined by the reverse PCR sequence‐specific oligonucleotide hybridization method (revPCR‐SSO) using LabType SSO Class I Locus A and Locus B kit , (One Lambda, ThermoFisher Scientific, Waltham, MA, USA), following the manufacturer's instructions. When only one allele was detected, the subject was considered homozygote …”
Section: Methodsmentioning
confidence: 99%